Ontogenetic and seasonal changes in the diets of the glowbelly Acropoma japonicum Gunther, 1859 in the south-eastern waters of Korea - Park, Joo Myun; Huh, Sung-Hoi (Indian Journal of Fisheries, 2018)
The dietary patterns of the glowbelly Acropoma japonicum Gunther, 1859 were studied based on 180 specimens collected during January to December 2006 off the south-eastern coast of Korea. The standard length (SL) of the specimens ranged from 3.0 to 10.3 cm. A. japonicum was found to be a benthopelagic predator that primarily consumed copepods and carid shrimps, but also preyed moderately on teleosts and euphausiids. The dietary composition of A. japonicum differed between length classes, with copepods and carid shrimps being dominant in the diet of small and large length class, respectively. The diets also were different among seasons, with the difference particularly being evident between warm (summer and autumn) and cold (winter and spring) seasons. Permutational multivariate analysis of variance (PERMANOVA) and analysis of similarities (ANOSIM) revealed significant dietary differences by size and season. These differences in the diets were related to first maturity in female and seasonal changes in water temperature.